Pengaruh ROA, ROE, TATTO Terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur Yang Listed Di Bursa Efek Indonesia Tahun 2020-2022) - Putri Anggraeni; Rani Afriyani; Widodo Ryan Setiaji; Muhammad Habil Habszy Masabrino (Jurnal Bintang Manajemen, 2023)
This study aims to determine the effect of ROA, ROE, TATTOO on PBV. The object studied in this study is a manufacturing company listed on the Indonesia Stock Exchange for the period 2020-2022. This type of research is quantitative research. The population in this study is Manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The research sample was selected using purposive sampling technique and obtained as many as 89 observational data. This study used secondary data obtained through the Annual Report. The data analysis technique in this study is multiple linear regression. The results showed that the ROA and TATTO variables had an effect on PBV, while the ROE variable had no effect on PBV.